Phenology of Bursera simaruba and Bursera tomentosa at a tropical dry forest of Chiapas, Mexico - Hernández-Rodríguez, Zuleima Guadalupe; Castro-Moreno, Marisol; González-Esquinca, Alma Rosa; de-la-Cruz-Chacón, Iván (Instituto de Ecología, A.C., 2021)
The genus Bursera is a characteristic component of the tropical dry forest (TDF) of Mexico, however, despite being relevant for the conservation and management of the species, its biology is little known, among them, their phenological patterns and their associations with seasonal factors. The aim of this research was to characterize the phenology of Bursera simaruba Jacq. ex L and Bursera tomentosa (Jacq.) Triana & Planch and to evaluate their relationship with environmental variables. The phenological study was realized in a protected area with tropical dry forest of the Central Depresion from Chiapas. Fifty adult trees of each specie were selected and the intensity of four reproductive phenophases (flower bud, open flower, fruit development and permanence of fruits) and three vegetative ones (leaf bud, mature leaves, senescence) were recorded using the Fournier method. Seasonality and synchrony in each phase were estimated by circular statistics calculating the mean vector (r) and the Rayleight test (Z). Also, the functional types of vegetative phenology were categorized and that of reproductive phenology. All the phenological stages were seasonal (r> 0.5), in both species, the flowering and leaf bud phenophases occurred in a short period while the vegetative and fruit production phenophases are the more extended stages. The reproductive and vegetative phenology of Bursera simaruba and B. tomentosa were very similar, and the most correlated environmental variables with them (rs ≥ 0.6) were temperature and humidity. These results allow to know the phenological dynamic of Bursera species in the TDF, and with this, to promote management and conservation strategies of these important species.